Teaching Literature in A Doll’s House Drama - Rahman, Izza Amalia; Mustofa, Mutmainnah; Putra, Irfan Susiyana; Moueed, Abdul (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
In education, teaching literature is an essential way to strengthen students’ character building. A kind of literature to teach character building is drama. Drama is literary work that contains so many characters. It can be used as a tool for character development to students who have been taught with literature. This article aims to discuss the characters of Nora Helmer (a woman lived in Victorian era when women had powerlessness) in A Doll’s House Drama written by Henrik Ibsen. The method used is descriptive qualitative. It concentrated on providing explanation in the form of description about Nora Helmer’s characters that could be taught as students’ character building. The analysis of Nora’s characters results several findings. Woman’s figure represented by Nora’s characters are loyal, love and compassion; obedient; care and helpful; patience and spirited; responsible; brave. The findings show that a woman at that time even though she had a lot of difficulties, she tried to solve the problem, she tried to be the best for her husband and family. But when she was disrespected, she had to be brave to uphold her dignity. This article expects the students can increase their good characters, competence, conscience, and compassion in learning language.